The efficacy and safety of submucosal tunnel endoscopic resection for the treatment of upper gastrointestinal submucosal tumors: a systematic review and meta-analysis - Liu, Hong; Ma, Qing; Zhu, Linlin (Frontiers in Oncology, 2025)
ObjectiveThe comprehensive systematic review was conducted to assess the efficacy and associated factors of submucosal tunnel endoscopic resection (STER) in the treatment of upper gastrointestinal submucosal tumor.MethodsDatabases including PubMed, Web of Science, CNKI, Wang Fang, VIP and Embase were electronically searched for studies on STER for the treatment of upper gastrointestinal submucosal tumors from inception to September 17, 2024. Two authors conducted the literature search independently. A third author resolved any inconsistencies raised between the two. Keywords were used for retrieval, and Boolean operators were used accordingly. The literature on treatment with STER and disease with upper gastrointestinal submucosal tumors will be included in the study. Statistical analysis was performed using Stata 16 software. χ2 test was used to analyze the heterogeneity among the studies. The fixed effects model and random effects model were used for meta-analysis. Standardized Mean Difference (SMD), Relative Risk (RR), and 95% confidence intervals (CI) were used to estimate clinical efficacy/effectiveness. Funnel plot symmetry was used to assess the risk of publication bias between studies.ResultsEight retrospective studies were ultimately incorporated into the meta-analysis. The experimental group was treated with STER. The control groups included patients receiving conventional endoscopic treatments such as ESD, EFTR, ESE, or LECS. The results of this analysis indicated no statistically significant differences between the intervention group and the control group in complete removal rates [RR=0.98 (0.94, 1.03), P>0.01], mean hospital stay [SMD=-0.40 (-0.89, 0.09), P>0.01], mean operation time [SMD=0.08 (-0.40, 0.57), P>0.01], or complication rates [RR=0.91 (0.44, 1.90), P>0.01]. Subgroup analysis identified age and tumor sizes as sources of heterogeneity in complication rates. In patients older than 55 years, STER exhibited a significantly lower risk of complications compared to traditional treatment modalities, with a risk ratio of 0.151 (95% CI: 0.041–0.558; P < 0.05). This indicates that STER may be a particularly beneficial option for this patient demographic.ConclusionsThe study found no significant differences in complete removal rate, mean hospital stay, mean operation time, and complication rate between STER and Traditional treatment. Nonetheless, a subgroup analysis of patients aged 55 and older uncovered a notable reduction in the incidence of complications among individuals undergoing STER for upper gastrointestinal submucosal tumors in comparison to the control group. These findings suggest that STER may constitute a more advantageous treatment option for elderly patients owing to its lower incidence of complications. There was no evidence of publication bias in the included literature, and the results demonstrated robustness following sensitivity analysis.